Perception of atrial fibrillation in dependence of neuroticism - Kranert, Malte; Benz, Annika Brunhilde Elisabeth; Shchetynska-Marinova, Tetyana; Hetjens, Svetlana; Liebe, Volker; Rosenkaimer, Stephanie L.; Dösch, Christina; Akın, Ibrahim; Borggrefe, Martin; Hohneck, Anna (Journal of psychosomatic research, 2020)
Objective - Atrial fibrillation (AF) is associated with a varying symptom burden, which ranges from completely unawareness to disabling conditions. The present cross-sectional study tried to assess if neuroticism is associated with a greater degree of perception of AF related symptoms. - Methods - 162 patients who were considered for catheter ablation of AF were included. AF related symptom burden was quantified according to the European Heart Rhythm Association (EHRA) score. Personality traits were assessed using the Big Five personality traits (5BT). - Results - Female patients reported higher symptom burden. Higher EHRA scores were furthermore associated with treatment with antiarrhythmic agents, digitalis, direct oral anticoagulants (DOAC), and antidepressant treatment, as well as suffering from heart failure or chronic kidney disease. Neuroticism showed a positive correlation to AF related symptom burden with significantly higher neuroticism scores in patients with higher EHRA scores (Rho = 0.41; 95%CI 0.26 to 0.53; p < .001), while no association was demonstrated for the other four personality traits. Multiple linear regression analysis revealed neuroticism as strongest independent predictor for symptomatic AF, followed by treatment with antiarrhythmic agents and DOAC. - Conclusions - Perception of AF related symptoms is a multifactorial process, which in our cohort was independently associated with neuroticism. Patients with higher symptom burden were also more likely to receive antiarrhythmic agents and DOAC, as well as antidepressants. - Trial registration - German registry for clinical studies (DRKS), DRKS00019007.
Gesehen am 08.08.2024